Stock Liquidity and the Pricing of Earnings: A Comparison of China’s Floating and Non-floating Shares - FANG, Lou (Institutional Knowledge at Singapore Management University, 2013)
The reform to convert non-floating shares to floating in China provides a setting in which shares are subject to different liquidity constraint. We show that the severity of this constraint is inversely related to the extent to which earnings information is reflected in the share prices. Specifically, before the reform, the transfer prices of non-floating shares reflect much less earnings information than the market prices of floating shares. After the reform, however, both types of transfer reflect more earnings information, although the weights are still less than that found in the market prices. Thus, China's unique setting shows that share liquidity affects the way earnings are priced in stock.